Surgical Repair of Ischemic Mitral Insufficiency in Combination with Left Ventricle Plasty - Rudenko, S. A.; Rudenko, A. V.; Yoffe, N. O.; Dyachenko, V. L. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Chronic ischemic mitral regurgitation is a frequent and severe complication after myocardial infarction. Its pathophysiological mechanisms explain the left ventricle remodeling, induce the papillary muscles displacement and change the angle of inclination of the valve leaflets. The presence of ischemic mitral insufficiency is independently associated with mortality and morbidity after myocardial infarction. In the recent years, at the National M. M. Amosov Institute of Cardiovascular Surgery, 42 patients underwent surgical combined interventions on the mitral valve and the left ventricle. All the patients underwent left ventricle plasty. The most frequent complication in the postoperative period was acute cardiovascular failure, which occurred in 25 (59.5 %) cases: 6 (42.9 %) cases after mitral defects plasty and 19 (67.8 %) patients after the valve replacement. The second most frequent complication was respiratory failure of II-III degree. In this patient cohort, respiratory failure in the postoperative period occurred in 5 (11.9 %) patients. Postoperative mortality after combined resection of the left ventricular aneurysm and surgical repair of ischemic mitral insufficiency was 9.5 % (4 cases). The difference in mortality after mitral valve plasty (14.3 %) and valve replacement (7.1 %) was statistically insignificant. Left ventricular aneurysm combined with ischemic mitral insufficiency contributes to the severity of the patients’ condition. Prognostic mortality (EuroSCORE) in this category of patients is 33.5 ± 5.4 %. Choosing the method for mitral insufficiency surgical repair does not affect postoperative mortality. Mortality is due to the initial severity in this group of patients.